Screening, isolation and purification of bioactive compounds with antibacterial activity against mycobacterium smegmatis - Mmushi, Tshepo Joseph (My University, 2011)
The leaves of fifteen plant species were collected from the Lowveld Botanical Garden in Nelspruit, Mpumalanga Province, South Africa. The collection was based on a list of plants and their ethnopharmacological information provided by the Phytomedicine Programme at the University of Pretoria. The dried leaves of the plants were powdered and extracted using hexane, dichloromethane, acetone and methanol. The extracts were screened for antibacterial activity against Mycobacterium smegmatis and Rhodococcus erythropolis. The acetone extract of Milletia stulhimannii was the most active, showing activity against Mycobacterium smegmatis and Rhodococcus erythropolis with MIC values 0.13 and 0.08 mg/ml, respectively. Acetone extracts for all plants had the lowest MIC values ranging between 0.11-1.25 mg/ml and 0.08-1.25 mg/ml for M. smegmatis and R. erythropolis, respectively. Milletia stulhimannii, Albizia gummifera, Xanthocercis zambesiaca and Barringtonia racemosa extracts have shown the greatest potential for anti-tubercolosis agents. These were all active against M. smegmatis with an average MIC value of acetone extracts of 0.13 mg/ml. Apodytes dimidiata was selected for the isolation of active compounds since its activity on qualitative antibacterial activity assays was highly prominent on TLC plates in comparison to the other plant extracts. Two compounds were isolated from A. dimidiata but after purification, their MICs were above 2.5 mg/ml indicating a possible loss of activity during purification. The preliminary NMR spectra analysis suggested that the compounds were a long fatty acid and a triterpene. Future work is required to elucidate the chemical structures of the latter compounds and to test the activity of these compounds against Mycobacterium tuberculosis.
Thesis (M.Sc. (Microbiology)) --University of Limpopo, 2011
Keywords: Bioactive compounds; Antibacterial activity; Mycobacterium smegmatis; 577.627; Environmental pollution; Water (pollution)